รูปแบบการสร้างเครือข่ายหมู่บ้านรักษาศีล 5 เพื่อการพัฒนาคุณภาพชีวิตของประชาชน จังหวัดนครราชสีมา - Wisut, Phrakhrusripariyattayarak (วารสารสันติศึกษาปริทรรศน์ มจร, 2018)
This objectives of this research were 1) analyzed the working principles of network the five precepts observing village, 2) analyzed correlative of the networking that integrated the tasks to improve quality of life for people in the five precepts observing village, 3) present the model of networking the five precepts observing village for improving people’s quality of life. Methodology is mixed between quantitative and qualitative research; the statistics that used are frequency, percentage, mean and standard deviation The research result is found that 1. the working principles of network the five precepts observing village; has corporate to networking under regulations, driven approach that consist the requirement and participation to encourage the five precepts observing village accordance with 1) principle of realization and participation as the network, 2) principle of create the obligations and manage the networking of five precepts observing village, 3) principle of correlative development of the networking of five precepts observing village and 4) principle of keep in the correlation and continue the networking of five precepts observing village 2. correlative of the networking that integrated the tasks to improve quality of life for people in the five precepts observing village in Nakhon Ratchasima Province such as 1) correlation of authority is the networking by integrated that tasks and participation that assigned, 2) correlation of regional is operate according to administrative conditions of 32 districts with Provincial Buddhist Monks Hierarchy in Nakhon Ratchsima, Provincial Buddhist Office of Nakhon Ratchasima, Village/Community has established their networking of five precepts observing. It is administration of regional, 3) correlation of issue; has plan, operate, assist, support, monitor the evaluation by their interested issue and lead to working in village, temple, community, organization, section, education institute to provide the activity accordance with determined issue